1992
DOI: 10.1056/nejm199210293271805
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure to Lead and Children's Intelligence at the Age of Seven Years

Abstract: Low-level exposure to lead during early childhood is inversely associated with neuropsychological development through the first seven years of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
234
1
5

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 491 publications
(246 citation statements)
references
References 27 publications
6
234
1
5
Order By: Relevance
“…In a number of cohort studies, in which the same children were followed from birth to school age, peak BPb was observed in the 2nd year of life, followed by decrease thereafter [22][23][24][25]. The present result (Table 2) seemed to be consistent with this finding, although ours is a cross-sectional design.…”
Section: Discussionsupporting
confidence: 90%
“…In a number of cohort studies, in which the same children were followed from birth to school age, peak BPb was observed in the 2nd year of life, followed by decrease thereafter [22][23][24][25]. The present result (Table 2) seemed to be consistent with this finding, although ours is a cross-sectional design.…”
Section: Discussionsupporting
confidence: 90%
“…When the Boston children were tested at 10 years of age (47), the verbal subscale of the WISC-R was more sensitive than the performance scale. In the Port Pirie study (52), all scales of the WISC-R were affected when the children were 7 years old, although the information and block design were the most sensitive. (18,28) (29) (30,31) (32) (33)(34)(35) (45), while performance at 10 years of age was most associated with lead levels at 2 years (47).…”
Section: Human Studiesmentioning
confidence: 95%
“…Numerous studies have shown that children with only moderately increased BPbs (10-15 µg/dL) suffer disproportionately from cognitive and neurobehavioral deficits, including lower intelligence quotient scores and diminished attention span, bilateral coordination, visual-motor control, upper-limb speed, dexterity, and fine motor skills (8)(9)(10)(11)(12)(13)(14)(15). In addition, there is mounting evidence of deleterious effects associated with BPbs even below 5 µg/dL; these include hearing loss, adverse hematologic effects, dental carries, and diminished cognitive and academic skills (16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%